2016
DOI: 10.1371/journal.pone.0149300
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Iodine Sufficiency and Moderate Insufficiency in the Lactating Mother and Nursing Infant: A Computational Perspective

Abstract: The Institute of Medicine recommends that lactating women ingest 290 μg iodide/d and a nursing infant, less than two years of age, 110 μg/d. The World Health Organization, United Nations Children’s Fund, and International Council for the Control of Iodine Deficiency Disorders recommend population maternal and infant urinary iodide concentrations ≥ 100 μg/L to ensure iodide sufficiency. For breast milk, researchers have proposed an iodide concentration range of 150–180 μg/L indicates iodide sufficiency for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…Studies have shown considerable variation in BMIC within and between individuals, and although no official guidelines exist for the cut-off for median BMIC, >75 μg/L has been suggested as adequate (Azizi & Smyth, 2009). However, higher cutoffs have been proposed (Fisher, Wang, George, Gearhart, & McLanahan, 2016), and studies from areas of sufficiency have reported median BMIC 150 to 180 μg/L (Delange, 2007;Dorea, 2002;Semba & Delange, 2001). The results of the present study suggest that a median BMIC of 84 μg/L might not be sufficient for 5-6 months EBF and PBF infants.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown considerable variation in BMIC within and between individuals, and although no official guidelines exist for the cut-off for median BMIC, >75 μg/L has been suggested as adequate (Azizi & Smyth, 2009). However, higher cutoffs have been proposed (Fisher, Wang, George, Gearhart, & McLanahan, 2016), and studies from areas of sufficiency have reported median BMIC 150 to 180 μg/L (Delange, 2007;Dorea, 2002;Semba & Delange, 2001). The results of the present study suggest that a median BMIC of 84 μg/L might not be sufficient for 5-6 months EBF and PBF infants.…”
Section: Resultsmentioning
confidence: 99%
“…A similar model demonstrated that the mean weight and length of boys increased by 70 g and 0.41 cm for every 0.5 mg/L increase in maternal UIC [ 42 ]. Fisher [ 43 ] reported that a moderate iodine deficiency in lactating women resulted in a 30% reduction of thyroxine in their infants, which played an important role in bone development. For another view, a study from Korea [ 44 ] found that excessive iodine intake of lactating women may be linked with hypothyroidism in their preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Iodine deficiency in nonpregnant women of reproductive age is also of concern because of the possibility of pregnancy. It is also important to ensure that nursing infants receive sufficient iodine from breast milk, although it is not clear that lactating women in the United States are at risk for iodine deficiency (51).…”
Section: Discussionmentioning
confidence: 99%